A genetic algorithm-based approach to design minicells for mass customisation manufacturing. (18th February 2008) - Badurdeen, Fazleena; Masel, Dale
Designing and deploying a manufacturing system that has the flexibility to deliver customised product at low cost and short turnaround times is one of the main challenges that must be overcome by potential mass customisers. Configuring the system as a collection of modules, by creating minicells that are dedicated to option families, which can be recombined as necessary is one approach to achieve this flexibility. This paper presents a genetic algorithm-based approach to design a minicell configuration for mass customisation. The method is illustrated using a numerical example and results are compared with those from traditional manufacturing cells. The findings are promising and show potential for further improvement to achieve higher flexibility and shorter delivery times for dynamic demand environments as seen in mass customisation.